Problematic internet use, depression, stress and anxiety amongadolescents in an urban area in South India: a cross sectional study - Rajanna, Kavya; Sathyanath, Shreyaswi M. (International Journal Of Community Medicine And Public Health, 2021)
Background: Internet usage is ubiquitous, especially among young population in urban India. The present study aims to assess the burden of problematic internet use and to determine its association with depression, anxiety and stress among adolescents in urban South India. We have also assessed the role of parental/care giver factors in internet usage among the adolescents. Methods: This was a school based cross sectional study among two high schools in urban field practice area. The students were administered validated questionnaire on sociodemographic details, parental/care giver factors, pattern of internet usage, problematic and risky internet use screening scale as well as depression, anxiety and stress scale-21.The descriptive data was analysed as proportions and associations were determined using Chi square tests. Results: 24% of students had PIU and this was significantly associated with stress, depression and anxiety. 33% had stress and class of studying was found to be the only significant determinant. Almost half (48%) had depression and class of studying, type of family as well as mother’s occupation were the significant determinants. Half (50%) had anxiety with the significant determinants being age, class of studying, type of family, type of school, religion and father’s education. The only common factor found to significantly affect internet usage was parental rule setting and supervision. Conclusions: Depression, stress and anxiety were associated with PIU. Setting and enforcing reasonable rules while maintaining trust and emotional support is essential to protect adolescents from the harmful effects of problematic internet usage.